Criminological Examination of Juvenile Presence in Criminal Proceedings (With a Perspective on the 2014 Afghanistan Offenses Adjudication Law) - Mohammad Abrahim Masoun; Mohammad Tariq Wamiq; Ali Asghar Modaber (Science and Education, 2024)
Psychological trauma, violence, aggression, and crime can be the outcomes of juvenile involvement in criminal proceedings. Therefore, adopting measures such as the specialization of criminal justice actors, establishing social centers for temporary custody, creating independent social centers, and developing educational and rehabilitative (corrective-therapeutic) programs can mitigate adverse effects on their future lives. The differential approach to juvenile offenses has been one of the major achievements of criminological activities in criminal proceedings over the past two centuries. Additionally, the existence of various international documents such as the “Convention on the Rights of the Child” and the “United Nations Standard Minimum Rules for the Administration of Juvenile Justice” (Beijing Rules) regarding the treatment of delinquent children and the efforts to encourage juveniles to reintegrate into society, along with state commitments in this regard, are also results of criminological and human rights endeavors. The consequences of juvenile involvement in criminal proceedings can be studied from the perspective of two branches of criminology (clinical and interactionist), both products of social reaction criminology, the consequences of juveniles’ involvement in criminal proceedings can be studied.